2011
DOI: 10.1021/jf104092e
|View full text |Cite
|
Sign up to set email alerts
|

Organic Synthesis of New Putative Lycopene Metabolites and Preliminary Investigation of Their Cell-Signaling Effects

Abstract: Tomato is the main dietary source of lycopene, a carotenoid that is known to have protective effects on health and whose metabolites could also be involved in bioactivity. Herein we present the first organic synthesis of two potentially bioactive lycopene metabolites, namely, 10'-apolycopen-10'-oic acid (6) and 14'-apolycopen-14'-oic acid (13), which were obtained in their (all-E) stereoisomeric forms using Wittig and Horner-Wadsworth-Emmons type coupling reactions. Both molecules are shown to up-regulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Apo‐6′‐, ‐8′‐, and ‐12′‐lycopenal standards were purchased from CaroteNature (Münsingen, Switzerland). Apo‐10′‐lycopenal, apo‐10′‐lycopenol, apo‐10′‐lycopenoic acid, apo‐14′‐lycopenal, apo‐14′‐lycopenol, apo‐14′‐lycopenoic acid, apo‐11‐lycopenal standards were synthesized previously . The glycerol phosphate oxidase assay was from Abliance (Compiegne, France).…”
Section: Methodsmentioning
confidence: 99%
“…Apo‐6′‐, ‐8′‐, and ‐12′‐lycopenal standards were purchased from CaroteNature (Münsingen, Switzerland). Apo‐10′‐lycopenal, apo‐10′‐lycopenol, apo‐10′‐lycopenoic acid, apo‐14′‐lycopenal, apo‐14′‐lycopenol, apo‐14′‐lycopenoic acid, apo‐11‐lycopenal standards were synthesized previously . The glycerol phosphate oxidase assay was from Abliance (Compiegne, France).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the recent characterization and study of carotene 99,10'-oxygenase in mammalian tissues has demonstrated that this enzyme can catalyze the cleavage of lycopene to form apo-10'-lycopenal, apo-10-lycopenol, and ALA from lycopene (14). Several reports, including our own, suggest that the biological activities of lycopene may be mediated in part by lycopene metabolites in vitro and in vivo (15)(16)(17)(18), which have displayed unique biological activities. A series of apo-lycopenals, including apo-10'-lycopenal, has recently been identified in human plasma (19).…”
Section: Introductionmentioning
confidence: 92%
“…The HWE reaction has also been used to prepare putative lycopene metabolites (Scheme 33) by desymmetrization of unsaturated dialdehydes [57].…”
Section: Lipidsmentioning
confidence: 99%